Burden of Malaria at Community Level in Children Less Than 5 Years of Age in Sokoto, Nigeria. - Ikpeama, Osita John, Igbineweka Osa Osazuwa, Ikpeama Emeka Andrew, Ikpeama Chinwe Joy, Ogwuegbu Juliet Uchechi, Ikpeama Chizoba Anthonia, Muazu Mary, Yahya Auwal, Mohammad Salisu (Sokoto Journal of Medical Laboratory Science)
Malaria fever a public health issue is the commonest manifestation and children aged less than 5 years are most vulnerable. A retrospective study which is aimed at determining the prevalence of malaria case in children less than five years. The data was collected from the health facility daily outpatient department register. The malaria testing was carried out according to World Health Organization (WHO, 2011) standard using microscopy and Malaria rapid diagnostic tests (RDTs), an immune chromatographic antigen- detection tests was the technique used in the course of research from July to September 2016. Result from this study shows that the percentage of malaria cases vary across the months June 94(15.9%), July 100(15.7%), August 207(18.1%), September 150(17.4%) and October 219(21.4%). The prevalence of malaria in children less than five years reported out of 4261 patients that used the facility in this period was 18.1%. Malaria among male children under the age of 5 years was 456(59.2%). Male had highest number 125,124 cases in October and August respectively. The female highest malaria cases were 94 and 83 in October and August respectively. The lowest cases of malaria among the male 60 occurred in the month of June while that of the female is 34 cases in the same month. Community participation and health education strategies promoting awareness of malaria and the importance of control measures should be implemented. The community should know the prevalence rate of the disease, its danger and how it can be prevented.